Influence of sustainability practices and green image on the re-visit intention of small and medium-size towns - Mercade-Mele, Pere; Molina-Gómez, Jesús; Sousa, María José (MPDI, 2020)
This study set a model to predict the effect of corporate social responsibility and green image on visit intention in small and medium-size towns (SMST). At present, there is a keen social awareness towards environmental problems, and cities are required to reduce their ecological footprint and make more sustainable use of natural resources. Increasingly, tourists are considering “green options” in their decision making. The questionnaire responses, obtained from a sample of 221 tourism in Malaga town (Spain) were analyzed using a Structural Equation Modelling (SEM) to test the research hypothesis related to the positive influence of sustainability practices, green image, trust with the intention of revisiting related to the loyalty of the destination. This study shows that there is a positive relationship between sustainability practices and re-visit intention and between the green image and re-visit intention, both directly and indirectly, through trust. Also, the fact that this relationship is more significant if it is part of the green image than if it is part of sustainability actions. To practice, this study provides managerial implications to help executives adopt green actions, thanks to their positive effects on tourist loyalty and the different way of manifesting this loyalty.
Keywords: Turismo-Aspectos ambientales; sustainability practices; Green Imagine; Trust; Re-visit intention; SMST; Structural equations model